Sensitivity analysis and parameter adjustment in a simplified physical wildland fire model. (December 2015) - Prieto, D.; Asensio, M.I.; Ferragut, L.; Cascón, J.M.
Highlights: A simplified physical 2D wildland fire model is summarized. Some aspects of the numerical techniques used to solve the model are outlined. The simplicity of the model and the numerical techniques proposed allow very competitive computational times. The model is applied to a well measured experimental example. A global sensitivity analysis of the model is performed in order to validate the simplications proposed. A parameter adjustment of the model applied to the experimental example is carried out. Abstract: A global sensitivity analysis and parameter adjustment of a simplified physical fire model applied to a well measured experimental example is developed in order to validate the model. The fire model is a simplified physical 2D wildland fire model with some 3D effects that takes into account the wind, the slope of the orography, the fuel load and type, the moisture content, the energy lost in the vertical direction and the radiation from the flames. The simplicity of the model and the numerical techniques proposed allow very competitive computational times.